Freeze-drying assisted synthesis of hierarchical porous carbons for high-performance supercapacitors. Issue 42 (24th September 2015) - Li, Yue; Liu, Qinglei; Kang, Danmiao; Gu, Jiajun; Zhang, Wang; Zhang, Di
Abstract : A novel method combining freezing-drying and self-assembly was developed to prepare carbon electrodes with optimized hierarchical pore structures. Abstract : A novel approach is reported to synthesize carbon foams with designable hierarchical porous structures for energy storage. The obtained carbons have an interconnected macroporous channel structure with narrow mesopores (3–5 nm in diameter) embedded throughout the carbon walls, providing low-resistance pathways for ion transportation to internal carbon surfaces. The obtained carbon electrodes can offer a capacitance up to 270 F g −1 at a current density of 0.1 A g −1 and especially an excellent high-rate performance with 222 F g −1 as the current density increases to 10 A g −1 . Additionally, the electrodes exhibit a long cycling life at a high current density up to 10 A g −1 .